1999
DOI: 10.1161/01.cir.100.suppl_2.ii-206
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Life Support to Left Ventricular Assist Device Bridge to Heart Transplant : A Strategy to Optimize Survival and Resource Utilization

Abstract: Background-The use of extracorporeal life support (extracorporeal membrane oxygenation [ECMO]) as a direct bridge to heart transplant in adult patients is associated with poor survival. Similarly, the use of an implantable left ventricular assist device (LVAD) to salvage patients with cardiac arrest, severe hemodynamic instability, and multiorgan failure results in poor outcome. The use of LVAD implant in patients who present with cardiogenic shock who have not been evaluated for transplantation or who have su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
103
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(111 citation statements)
references
References 6 publications
5
103
0
3
Order By: Relevance
“…The incidence of right ventricular failure after LVAD implantation was higher in patients with preoperative PCPS, 5 and preoperative circulatory support was the most significant risk factor for mechanical right ventricular support after LVAD implantation. 14 In the present series, more patients with preoperative PCPS developed right ventricular failure, which required prolonged i.v.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The incidence of right ventricular failure after LVAD implantation was higher in patients with preoperative PCPS, 5 and preoperative circulatory support was the most significant risk factor for mechanical right ventricular support after LVAD implantation. 14 In the present series, more patients with preoperative PCPS developed right ventricular failure, which required prolonged i.v.…”
Section: Discussionmentioning
confidence: 93%
“…4, 5 The impact of preoperative PCPS on LVAD support, however, remains inconclusive. McCarthy et al found that prior PCPS was a significant risk factor for death after LVAD implantation, 13 whereas Pagani et al reported that preoperative PCPS was not a risk factor for death after LVAD implantation.…”
Section: Discussionmentioning
confidence: 99%
“…4) In this retrospective study, we analyzed data from patients who required PCPS to determine early predictive factors for successful weaning from PCPS in patients with low cardiac output syndrome after cardiovascular surgery.…”
mentioning
confidence: 99%
“…The temporary support should guarantee the resuscitation and resolution of organ dysfunction before LVAD implant, as well as performance of an adequate transplant evaluation (55).…”
mentioning
confidence: 99%